2000
DOI: 10.1054/bjoc.1999.1053
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma in the first-line therapy of ovarian cancer: a randomized phase III trial

Abstract: Intraperitoneal treatment with interferon-γ (IFN-γ) has been shown to achieve surgically documented responses in the second-line therapy of ovarian cancer. To assess its efficacy in the first-line therapy, we conducted a randomized controlled trial with 148 patients who had undergone primary surgery for FIGO stage Ic–IIIc ovarian cancer. In the control arm women received 100 mg m−2cisplatin and 600 mg m−2cyclophosphamide, the experimental arm included the above regimen with IFN-γ 0.1 mg subcutaneously on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
129
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(137 citation statements)
references
References 19 publications
4
129
0
4
Order By: Relevance
“…IFNg is not spontaneously secreted by ovarian tumors (Nash et al, 1998), which release several other cytokines involved in tumor progression or autocrine loops (Naylor et al, 1993;Wu et al, 1993;Hartenbach et al, 1997;Mesiano et al, 1998). In addition, IFNg has been shown to exert antitumor effects on ovarian cancer both in vitro (Kost et al, 1999) and in vivo (Windbichler et al, 2000), further suggesting that IFNg release from lymphoid cells triggered by biologically active IL-18 could inhibit ovarian tumor growth. The finding that D3pro-IL-18 cannot be cleaved by caspase-1 or -4 to a biologically active form, but retained the capacity to physically interact with caspase-1, suggested that it may inhibit classical pro-IL-18 processing.…”
Section: Discussionmentioning
confidence: 99%
“…IFNg is not spontaneously secreted by ovarian tumors (Nash et al, 1998), which release several other cytokines involved in tumor progression or autocrine loops (Naylor et al, 1993;Wu et al, 1993;Hartenbach et al, 1997;Mesiano et al, 1998). In addition, IFNg has been shown to exert antitumor effects on ovarian cancer both in vitro (Kost et al, 1999) and in vivo (Windbichler et al, 2000), further suggesting that IFNg release from lymphoid cells triggered by biologically active IL-18 could inhibit ovarian tumor growth. The finding that D3pro-IL-18 cannot be cleaved by caspase-1 or -4 to a biologically active form, but retained the capacity to physically interact with caspase-1, suggested that it may inhibit classical pro-IL-18 processing.…”
Section: Discussionmentioning
confidence: 99%
“…Like IFNg, retinoic acid plays an important role in the regulation of di erentiation and cell growth control, respectively (Evans and Kaye, 1999;Rohwedel et al, 1999). These properties have lead to the application of retinoic acid and IFNg in the therapy of certain leukemias and ovarian cancer (Chelbi-Alix and Pelicano, 1999;Windbichler et al, 2000). The major e ect of IFNg in tumour therapy is attributed to its capacity of enhancing immunogenicity by up-regulation of cell surface antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons exert inhibitory e ects on tumour cell growth and recently it was described that IFNg improved survival of ovarian carcinoma patients (Windbichler et al, 2000). Therefore we tested the e ects of IFNg on H-REV107-1 expression in human Figure 1 Down-regulation of H-REV107-1 in human ovarian carcinomas.…”
Section: Down-regulation Of H-rev107-1 In Human Ovarian Carcinoma Celmentioning
confidence: 99%
“…32,33 In addition, exogenous IFN-␥ exerts antitumor effects on ovarian cancer in vitro 34 and in ovarian cancer patients. 35,36 The antitumor effects of IFN-␥ have been related to direct antiproliferative effects, to immunomodulatory functions, to upregulation of antiangiogenic factors, such as monokine-inducible interferon-␥ (MIG) or interferon-inducible protein (IP)-10, 37 and in some tumors also to downregulation of the pro-angiogenic factor VEGF. 38 Recent evidence obtained by gene transfer approaches indicates that IL-18 may exert an antitumor function in murine tumor models in vivo and that these functions are related to IFN-␥ production and antiangiogenic effects.…”
Section: Discussionmentioning
confidence: 99%